Financial constraints, newly founded firms and the financial crisis - Julia Hirsch; Uwe Walz (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2017)
This paper aims to analyze the effects of financial constraints and the financial crisis on the financing and investment policies of newly founded firms. Thereby, the analysis adds important new insights on a crucial segment of the economy. We make use of a large and comprehensive data set of French firms founded in the years 2004-2006, i.e. well before the financial crisis. Our panel data analysis shows that the global financial crisis imposed a shock (mostly demand-driven) on the financing as well as on the investments of these firms. Moreover, we find that financially constrained firms use less external debt financing and invest smaller amounts. They also rely on less trade credit. With regard to bank financing, newly founded firms which are more financially constrained accumulate less bank debt and repay initial bank debt slower than their non-financially constraint counterparts. Finally, we find that financially constrained firms are affected to a smaller degree by the financial crisis than their less financially constrained counterparts.
urn:nbn:de:hebis:30:3-453763
Keywords: D92; G32; 330; financial constraints; financial crisis; financing decisions; investment decisions; newly founded firms